Pengaruh Persepsi, Tempat Tinggal dan Ukuran Keluarga Terhadap Minat Mahasiswa Agribisnis Universitas Diponegoro Untuk Bekerja di Bidang Pertanian - Widya Putri, Alberte Nissa; Mariyono, Joko; Setiyawan, Hery (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Agribusiness students, as young generation with agricultural knowledge, were expected to have a positive outlook and interest in working in the agricultural sector. This study aimed to describe the perception and interest of Agribusiness students at Diponegoro University in working in agriculture, as well as to analyze the influence of perception, residence, and family size on their interest in working in the agricultural sector. The research was conducted between April and May 2025. The method used was a survey. Primary data were obtained through the distribution of questionnaires to respondents, while secondary data were obtained from literature related to the topic. Sampling was carried out using simple random sampling techniques among Agribusiness students at Diponegoro University, with 60 students from each cohort of 2021 and 2022. Data collection used closed questionnaires. Data analysis was performed using quantitative descriptive methods; perception and interest were measured using a Likert scale, while the influence of perception, residence, and family size was analyzed using multiple linear regression. The results showed that the level of perception and interest of Agribusiness students in working in agriculture was in the high category, with respective percentages of 69.17% and 63.33%. The analysis results indicated that all variables influenced interest simultaneously. The perception variable influenced students’ interest partially, while the residence and family size variables did not influence the interest of Agribusiness students at Diponegoro University in working in the agricultural sector.